Maximum torque of combination threats for spur gear based on AGMA and JGMA standards - Wu, Jia Hang (2014)
This thesis is an approach to investigate the transformation curve of gearing safety. Two types of tooth failures are known to happen to spur gears. There are tooth bending failure (breakage) and tooth surface pitting failure. The focus of this study however will be on the JGMA and AGMA standards of gearing. Different methods were used to gather relevant data from both standards. JGMA data were gathered from a source in the internet while AGMA data were calculated with the aid of Autodesk Inventor spur gear component generator 2013. The most important data is the allowable torque applied on the gear tooth which can be distinguished into causing either one of the tooth failures mentioned above. Several materials selected from the JGMA and AGMA standards with high value of allowable contact stress compared to its allowable bending stress have a transformation curve from surface durability to bending strength when its torque values are plotted against number of teeth. This allows the forming of a combination threats curve for the material. The curves are useful in determining the maximum torque that can be applied on the spur gear before failures occur. The threat combination curves are then further developed into charts that include other parameters like power, angular velocity and pitch diameters.